Fuzzy Sliding Mode Control for Photovoltaic System - Mounir Derri; Mostafa Bouzi; Ismail Lagrat; Youssef Baba (Institute of Advanced Engineering and Science, 2016)
In this study, a fuzzy sliding mode control (FSMC) based maximum power point tracking strategy has been applied for photovoltaic (PV) system. The key idea of the proposed technique is to combine the performances of the fuzzy logic and the sliding mode control in order to improve the generated power for a given set of climatic conditions. Different from traditional sliding mode control, the developed FSMC integrates two parts. The first part uses a fuzzy logic controller with two inputs and 25 rules as an equivalent controller while the second part is designed for an online adjusting of the switching controller’s gain using a fuzzy tuner with one input and one output. Simulation results showed the effectiveness of the proposed approach achieving maximum power point. The fuzzy sliding mode (FSM) controller takes less time to track the maximum power point, reduced the oscillation around the operating point and also removed the chattering phenomena that could lead to decrease the efficiency of the photovoltaic system.